Bacterial Communities and Their Role in Bacterial Infections - Olga I. Guliy; Stella S. Evstigneeva (Frontiers in Bioscience-Elite, 2024)
Since infections associated with microbial communities threaten human health, research is increasingly focusing on the development of biofilms and strategies to combat them. Bacterial communities may include bacteria of one or several species. Therefore, examining all the microbes and identifying individual community bacteria responsible for the infectious process is important. Rapid and accurate detection of bacterial pathogens is paramount in healthcare, food safety, and environmental monitoring. Here, we analyze biofilm composition and describe the main groups of pathogens whose presence in a microbial community leads to infection (Staphylococcus aureus, Enterococcus spp., Cutibacterium spp., bacteria of the HACEK, etc.). Particular attention is paid to bacterial communities that can lead to the development of device-associated infections, damage, and disruption of the normal functioning of medical devices, such as cardiovascular implants, biliary stents, neurological, orthopedic, urological and penile implants, etc. Special consideration is given to tissue-located bacterial biofilms in the oral cavity, lungs and lower respiratory tract, upper respiratory tract, middle ear, cardiovascular system, skeletal system, wound surface, and urogenital system. We also describe methods used to analyze the bacterial composition in biofilms, such as microbiologically testing, staining, microcolony formation, cellular and extracellular biofilm components, and other methods. Finally, we present ways to reduce the incidence of biofilm-caused infections.